The modernisation of Indonesian naval forces in Jokowi era - Noraini Zulkifli; Muhamad Nazrul Basar; Azrul Azlan Abdul Rahman (Penerbit Universiti Kebangsaan Malaysia, 2020)
As an archipelago country, Indonesia has faced a lots of threats from the sea. Because of that, Indonesia has implemented Global Maritime Axis Policy (GMA) as a new strategy to protect its national interest and sovereignty. One of the GMA objective is to modernise Indonesia Naval Force. Using data and research findings from 2014- 2018, this article will debate about the modernization of Indonesia naval force under Jokowi Administration. This study has three objectives, namely toexplains the Indonesia naval capabilities, toanalyse the development of Indonesian naval force and to analyse the evolving of Indonesian navy doctrine. The findings reveal that first, Indonesia’s government has taken in an effort to get in the linkages between the changing contours, its function in the area, which, shifted, is being backed through its naval modernisation and expansion, and second, Indonesia has collectively doubled their military spending with warships, maritime patrol aircraft, radar systems, submarines and naval defence systems based on their Minimum Essential Forces (MEF) doctrine so that Tentara Nasional Indonesia-Angkatan Laut (TNI-AL) capable an enhance the Green Water Navy concept.